2011
DOI: 10.1002/mrm.22917
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and ex vivo MR imaging of slowly cycling melanoma cells

Abstract: Slowly cycling cells are believed to play a critical role in tumor progression and metastatic dissemination. The goal of this study was to develop a method for in vivo detection of slowly cycling cells. To distinguish these cells from more rapidly proliferating cells that constitute the vast majority of cells in tumors, we used the well‐known effect of label dilution due to division of cells with normal cycle and retention of contrast agent in slowly dividing cells. To detect slowly cycling cells, melanoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A determination of the lowest level of grafted cell that can be detected with the proposed method is essential for the clinical translation. In our previous work, we proposed a protocol to determine the sensitivity of T2‐weighted sequences for the detection of the iron oxide particles. We are adopting this technique for the SWIFT acquisition protocol and will report the results in a separate publication.…”
Section: Discussionmentioning
confidence: 99%
“…A determination of the lowest level of grafted cell that can be detected with the proposed method is essential for the clinical translation. In our previous work, we proposed a protocol to determine the sensitivity of T2‐weighted sequences for the detection of the iron oxide particles. We are adopting this technique for the SWIFT acquisition protocol and will report the results in a separate publication.…”
Section: Discussionmentioning
confidence: 99%
“…One might anticipate that a simple explanation for the distribution of label in tumors could be that label‐retaining regions contain slowly proliferating cells, while regions that have lost the cellular label represent rapidly dividing cells . Our label distribution maps, in this case, would in essence be cell proliferation maps.…”
Section: Discussionmentioning
confidence: 99%
“…We use cellular MRI and optical projection tomography (OPT) to map the distribution of a cellular label in two different mouse glioma tumors generated by intracranial injections of labeled tumor cells. The cellular label (iron oxide in the case of MRI ; a fluorescent label in the case of OPT) is diluted over time through cell division and, therefore, lost from quickly dividing cells, but retained in slowly cycling or nonproliferating cells . Consequently, the maps we obtain may reflect differences in the proliferative history of cells throughout the tumor.…”
mentioning
confidence: 99%
“…This is because the iron nanoparticles are diluted over time in dividing cells, leading to loss of signal and therefore loss of cell detection. However, we, and others, have shown that the retention of iron particles in nonproliferative, or slowly cycling, cancer cells can be exploited to detect particular cancer cell populations ( 16 18 ). In this paper, we use cellular MRI to study CTR in a novel model of breast cancer metastasis to the brain.…”
Section: Introductionmentioning
confidence: 99%